Analisis Histologis Hati Ikan Asang (Osteochilus hasseltii C.V.) di Danau Maninjau dan Danau Singkarak, Sumatera Barat - Ummul Fadhilah Lubis; Netty Marusin; Indra Junaidi Zakaria (Universitas Andalas, 2014)
Histological analysis of liver of hard-lipped barb (Osteochilus hasseltii C.V.) was conducted from March to October 2013 at the Laboratory of Animals Structure and Development, Department of Biology, Faculty Sciences, Andalas University, Padang. Those fish samples were collected form Maninjau and Singkarak Lakes, West Sumatra. The liver tissue were isolated, fixated, dehydrated, planted on paraffin and colored by Haematoxilyn-eosin. Cell Structure and forms were described based on Microscopic tissue study. Results found that the histological damage of fish liver from Maninjau showed three storeys of Hypertrophy, lysis, and necrosis, while Singkarak showed two storeys of hypertrophy and lysis. Those results may indicate that hard-lipped barb from the two lakes had been conminated by some pollutants.Keywords: Osteochilus hasseltii, histopatology, liver, Singkarak Lake, Maninjau Lake.